Creating Business Magic - Morey, David; Burger, Eugene; McLaughlin, John (Ascent Audio, 2018)
Business strategies from the world's greatest magicians: This book takes everything that three remarkable authors-a corporate strategist, the former acting director of the CIA, and a world-renowned magician-have learned about magic and packs it into a unique framework that captures the best of this art form and relates it directly to key lessons applicable to a wide variety of business enterprises. The authors' objective is not to create a new generation of magicians, but to adapt nine strategies of the world's greatest magicians and inspire boundless imagination, bolster innovation, energize leadership, and spark success in any business. At the core of Creating Business Magic is the belief that imagination can make magicians of us all. Magic and disruptive innovation: Each chapter opens with a scenario depicting a pivotal historic moment in magic-from Harry Houdini to Doug Henning to Penn and Teller to David Copperfield-and uses it as a starting point to explore how the magical technique employed can create a fertile environment for industry disruptive innovation and propel a company light years ahead of the competition.